2021
DOI: 10.1002/anie.202014348
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Mapping of Glutathione within Intracranial Tumors through Interlocked MRI Signals of a Responsive Nanoprobe

Abstract: Studies reveal that malignant tumors feature uneven distributions of some key biomarkers across the entire tumorous region. Nevertheless,o nly very limited progress has been made towards non-invasive and quantitative detection of tumor-specific biomarkers in vivo,e specially with clinically compatible imaging modalities.R eported here is an Fe 3 O 4 nanoparticle-based glutathione (GSH) responsive magnetic resonance imaging (MRI) probe that can form particle aggregates within tumors in vivo to give rise to stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 46 publications
0
47
0
Order By: Relevance
“…However, it exhibited dramatically enhanced T 2 enhancement in GSH-rich environment as GSH can reduce the disulfide bonds embedded in the peptide sequence to generate thiol groups that react with the maleimide groups from the adjacent USPIO particles to glue them together. It was further demonstrated that such GSH-induced particle aggregation could give rise to interlocked T 1 and T 2 signal variations, which were proven to quantitatively correlate with GSH concentration to enable the GSH mapping of intracranial tumor in vivo (Zhang et al, 2021).…”
Section: Outstanding Mri Performancementioning
confidence: 97%
“…However, it exhibited dramatically enhanced T 2 enhancement in GSH-rich environment as GSH can reduce the disulfide bonds embedded in the peptide sequence to generate thiol groups that react with the maleimide groups from the adjacent USPIO particles to glue them together. It was further demonstrated that such GSH-induced particle aggregation could give rise to interlocked T 1 and T 2 signal variations, which were proven to quantitatively correlate with GSH concentration to enable the GSH mapping of intracranial tumor in vivo (Zhang et al, 2021).…”
Section: Outstanding Mri Performancementioning
confidence: 97%
“…Precise diagnosis is the prerequisite for successful therapy, and to avoid false‐positive signals it is important to provide smart fluorescent probes which only respond to some specific disease‐related stimuli. [ 188,189 ] Such NIR‐II probes based on Ag 2 S SNCs were designed by Wang and co‐workers for accurate diagnosis of traumatic brain injury, acute myeloid leukemia, and cancer. [ 94,190,191 ] Outside the target region, the fluorescence of the nanoprobe was in the “off” state owing to the fluorescence resonance energy transfer (FRET) from Ag 2 S SNCs to the attached A1094 chromophore.…”
Section: Applications Of Nir‐ii Emitting Sncs In Biomedical Imaging T...mentioning
confidence: 99%
“…Medical imaging is one of the most important means of non-invasive studies ( Yang et al, 2017 ; Zhang et al, 2019 ; Zhang et al, 2020 ; Zhao et al, 2021 ). Especially, magnetic resonance imaging (MRI), one of the clinically compatible imaging modalities, have led to improved accuracy in the detection and characterization of central nervous system diseases, which can provide images of anatomical structure of the brain with high spatial resolution for studying pathologic foci ( Iima and Le Bihan, 2016 ; Fan, 2021 ; Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%